Aquatic biophysical inventory of major tributaries in the AOSERP study area Vol I ... - Sekerak, A. D. (University of Alberta Library, 1980)
This report summarizes and compares the physical characteristics of nine streams within five watersheds (Firebag, Muskeg, Steepbank, MacKay, and Ells) in the AOSERP study area. The distributions and relative abundances of fish in each stream and watershed are also described and related to the physical characteristics that tend to promote or limit sport fish production. The system of reach classification and biophysical measurements developed by Chamberlin and Humphries (1977) was used throughout the present study. The detailed results of this study are presented in the accompanying atlas that forms Volume II of this report (Walder et al. 1980). From 16 to 24 species of fish were found in each watershed. Forage fish (lake chub, pearl dace, longnose dace, trout-perch, brook stickleback, slimy sculpin) and white and longnose suckers were the most abundant fish in every stream or river studied. The most important and widespread sport fish present were (in order of decreasing abundance) arctic grayling, northern ...